ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI PRODUKSI BUAH MANGGIS DI DESA NEGERI GUGUNG KECAMATAN SIBOLANGIT KABUPATEN DELI SERDANG - Marahadi Siregar (JASA PADI, 2019)
Mangosteen fruit is a round fruit the size of a tennis ball, slightly hard and stiff skin with a purplish red color. Mangosteen fruit has a sweet taste, smooth skin, bright color, and its size is always attractive. This plant is a regional superior crop which has begun to be scarce in Indonesia especially North Sumatra. This study aims to: determine and analyze the effect of factors of production (land area, seedlings, fertilizer, and labor) onmangosteen fruit production in the village of Negeri Gugung, Sibolangit District, Deli Serdang Regency. The data used are primary data sourced from 39 mangosteen fruit farmers, by providing a questionnaire list. The research model is a quantitative model using multiple linear regression analysis techniques, using the SPSS program version 16.0. From the results of the study showed that the area of land, seeds, and labor, had a significant influence on the production of mangosteen fruit in Gugung Negeri Village, Sibolangit District, Deli Serdang Regency, but fertilizer did not have a significant effect on mangosteen production. The coefficient of determination R2 = 0.992 can be interpreted that the production of mangosteen fruit by 99.2% can be influenced by land area, seedlings, and labor.